Achieving high-efficiency emission depletion nanoscopy by employing cross relaxation in upconversion nanoparticles. Issue 1 (December 2017) - Zhan, Qiuqiang; Liu, Haichun; Wang, Baoju; Wu, Qiusheng; Pu, Rui; Zhou, Chao; Huang, Bingru; Peng, Xingyun; Ågren, Hans; He, Sailing
Abstract Stimulated emission depletion microscopy provides a powerful sub-diffraction imaging modality for life science studies. Conventionally, stimulated emission depletion requires a relatively high light intensity to obtain an adequate depletion efficiency through only light–matter interaction. Here we show efficient emission depletion for a class of lanthanide-doped upconversion nanoparticles with the assistance of interionic cross relaxation, which significantly lowers the laser intensity requirements of optical depletion. We demonstrate two-color super-resolution imaging using upconversion nanoparticles (resolution 66 nm) with a single pair of excitation/depletion beams. In addition, we show super-resolution imaging of immunostained cytoskeleton structures of fixed cells (resolution 82 nm) using upconversion nanoparticles. These achievements provide a new perspective for the development of photoswitchable luminescent probes and will broaden the applications of lanthanide-doped nanoparticles for sub-diffraction microscopic imaging. Upconversion nanoparticles, which do not suffer from the photophysical artifacts that limit fluorescent molecules, offer an exciting opportunity for biological super-resolution imaging. Here, Zhan et al. develop an efficient STED mechanism using optimized lanthanide upconversion nanoparticles, enabling cytoskeleton nanoscopic imaging.